The Mufti of Jerusalem and the Nazis: the Berlin years - Gensicke, Klaus (Vallentine Mitchell, 2011)
Amin al-Husaini is undeniably one of the key figures of the 20th century. He was the religious head of the Palestinian Muslims for 16 years, their political leader for 30 years, and, for a time, he was the most important representative of the Arab world. Now available in paperback, this book examines the time that Amin al-Husaini spent in Nazi Germany from 1941 to 1945. It looks at what the Mufti was hoping to gain politically and ideologically while he was there. The book is directed primarily at the four years which the Mufti of Jerusalem, with his staff of some 60 persons and a secret servi